A nineteenth-century adventure revisited: The account of the young Charles Darwin on board H. M. S. Beagle. A comparative analysis of chapters III to XVII of Charles Darwin's "Voyage of the Beagle" and four translations into Spanish. - Paoletti, Elisa. (University of Ottawa (Canada), 2001)
This comparative analysis presents Charles Darwin's The Voyage of the Beagle and four translations into Spanish. This travel account seems to have been rather overshadowed by the greater popularity of The Origin of Species but its stance as the first book in Darwin's prolific career and the paramount importance of having been the vehicle used by its author to introduce his incipient evolutionary ideas pose it as a very interesting project to embark upon. The Voyage of the Beagle, published for the first time in 1839, presents an unusual combination of scientific observations and reflections by the young traveller where Darwin's form of expression is a rich source for discourse analysis. This research focuses on only three, namely voices, negation and multilingualism. They are deemed as the most salient features of discourse in the source-language text and, therefore, the way in which they were rendered in the translations is observed and reflected upon. The detailed study of the decisions taken by the translators or editors according to their translation projects reveals that the salient discourse features of the source-language text were often overlooked. Thus, their rendering in Spanish modified Darwin's image as a narrator in the process. Moreover, despite the fact that these decisions have been greatly influenced by the place of publication and their target readership, many of the choices made throughout the translations show a lack of uniformity and coherence towards what they seemed to be trying to achieve within the framework of their translation projects.
Keywords: Literature, Romance.